THE IMPLEMENTATION OF COOPERATIVE LEARNING TYPE TEAMS GAME TOURNAMENT (TGT) METHOD TO IMPROVE STUDENTS MOTIVATION IN LEARNING ENGLISH - Pransiska, Ira Setia (PROJECT (Professional Journal of English Education), 2021)
The objective of this research is to describe the implementation of teams game tournament in learning English at SMP Pasundan 1 Cimahi. The research using descriptive qualitative method, and took 33 samples from seventh grade students. The writer collected data by interviewing and spreading questionnaires asked the students motivation which have 10 items adopted from Muhlisin, (2018). Percentage and descriptive explanations are applied in data processing. Based on this study, the writer found that; 1. The students became more active in learning activities, 2. The student’s teamwork and courage were increasing while discussing group time, and 3. The materials were easier to be accepted and understood by students. Those results indicated that the implementation of this method has enhanced the interest of students in learning English. From the questionnaires and interviews most of  the students choose to agree statements too. So, it showed us that the implementation of cooperative learning type teams game tournament method was successfully improving student’s motivation in learning English.Keywords:  Cooperative Learning, Teams Game Tournament, Students Motivation